Study on Detoxification Effect of Fermentation on Cyanide Content of Cassava Tuber - Iwuoha, G. N.; Ubeng, G. G.; Onwuachu, U. I. (New Innovations in Chemistry and Biochemistry Vol. 1, 2021)
The purpose this research therefore is to investigate the detoxification potential of fermentation, on the toxic (cyanide) content of cassava tuber. Cassava is a staple food in tropical nations for about 800 million people. The tuber, which is mostly starch, includes a high concentration of cyanogenic glycosides, which are hydrolyzed by enzymes to produce hydrocyanic acid. The fermentation process is achieved by soaking freshly peeled cassava tuber and the fermentation of grated cassava tuber hence, two fermentation treatments. This fermentation treatments were carried out at intervals of 2 days by using 20g of the sample portions of the fresh cassava tuber (UM 8082), which initially contained as high as 160.46mg/HCN/kg of the tuber. The pH values of the medium were measured daily to correlate it with on-going events. The Knowles and Watkin’s method of steam distillation technique was used to analyze the HCN (Hydrogen cyanide). Based on the experimental results obtained, there was a remarkable drop or reduction of this toxic principle in the tuber. Prolonged period of fermentation (5 to 6 days) and favourable pH medium 4.0 to 4.5) was found to effect tremendously HCN removal. In fact, 94.7% reduction that is 8.45 Mg/kg and 81.3% reduction that is 28.70mg/kg was achieved for the soaked and grated cassava tubers respectively. These values being below the recommended value 30mg/kg for safe cyanide level in food-stuff indicates that fermentation is an effective (and economic) method for detoxification of cassava tuber for human consumption. ©JASEM